BOOK REVIEW OF ECSTATIC WONDER OF ALLAMAPRABHU BY BASAVARAJ NAIKAR - Kanta Galani (UNHI PRESS, 2025)
Ecstatic Wonders of Allamaprabhu contains an English Translation of Allamaprabhu’s 582 vachanas from Kannad along with their critical analyses for the benefit of the international and national reader from Naikar’s point of view. It is useful to all those Indologists and Orientalists, who are interested in comparative global philosophy, mysticism, and literature. Allamaprabhu was a great mystic and super Sivayogi of twelfth-century Karnataka, India and easily comparable to other religious and mystic poets of the world like Kabiradasa, Namdev, Jnanadev, Chaitanya, Sri Aurobindo, John Donne, George Herbert, St. Augustine and Swedonberg and so on.